Pengaruh Bentuk Briket Blotong Terhadap Lama Waktu Mendidihkan Air dan Lama Membara - Eliza Alphan; Lilik Hendrarini; Y.B. Kamat Kartono (Poltekkes Kemenkes Yogyakarta, 2011)
Blotong as one of the wastes produced by sugar industries up to now has not been processed and managed adequately and so that raise people concern. Actually the waste can be utilized as biocharcoal briquette and be used as alternative fuel. Based on this, the purpose of this research is to know whether various shapes (i.e. spherical, cylindric, and cube) of the blotong briquette has diferent water boiling time and smouldering time by conducting an experiment which was following post test only design. The blotong were taken from Madukismo sugar industry in Tirtonirmolo Bantul. The study results showed that the average time for water boiling observed from the cylindric briquette (454,70 seconds) was the fastest compared with the other two; and the average smouldering time recorded from spherical briquette was the longest (i.e. 1805,30 seconds). Both of the results, when analyzed with one way anova test gained p-value lower than 0,05 which can be interpreted that the time differences between the three shapes were significant. Based on the results, the sugar industry as well as the people living nearby are advised to utilize the blotong. Further study to reveal if fresh and old blotong has different briquette quality is needed to carry on.